The creation of Wing Chun : a social history of the Southern Chinese martial arts - Judkins, Benjamin N., 1975-; Nielson, Jon, 1963- (Albany : State University of New York Press, 2015)
Looks at southern Chinese martial arts traditions and how they have become important to local identity and narratives of resistance.
The Past Is PrologueWing Chun as a Commodity in the Global Marketplace; Two Visions of the Wing Chun Community; Notes; Glossary; Works Cited; Index.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Martial arts -- China; Kung fu -- China; Kung-fu -- Chine; GAMES -- Gambling -- Sports; SPORTS & RECREATION -- Business Aspects; SPORTS & RECREATION -- Essays; SPORTS & RECREATION -- History; SPORTS & RECREATION -- Reference; TRAVEL -- Special Interest -- Sports; Kung fu; Martial arts; China